CD7-positive leukemic blasts with DNMT3A mutations predict poor prognosis in patients with acute myeloid leukemia - Bai, Yanliang; Sun, Xiaobai; Li, Mengyi; Niu, Xiaona; Cao, Weijie; Niu, Junwei; Xiao, Xingjun; Chen, Yuqing; Sun, Kai (Frontiers in Oncology, 2024)
Background: DNMT3A mutations can be detected in premalignant hematopoietic stem cells and are primarily associated with clonal hematopoiesis of indeterminate potential; however, current evidence does not support assigning them to a distinct European Leukemia Net (ELN) prognostic risk stratification. CD7 is a lymphoid antigen expressed on blasts in approximately 30% of acute myeloid leukemia (AML), and its role in AML remains unclear and depends on subgroup evaluation. This study investigated the prognostic value of DNMT3A mutation combined with CD7 expression in AML.We retrospectively analyzed the clinical data of 297 newly diagnosed non-M3 AML patients. According to the DNMT3A mutation and CD7 expression in AML cells, patients were divided into the DNMT3A-mutated/CD7-positive (CD7+), DNMT3A-mutated/CD7-negative (CD7-), DNMT3A-wild-type/CD7+, and DNMT3A-wild-type/CD7-groups.The DNMT3A-mutated/CD7+ group had lower complete remission rates and higher relapse rates. Importantly, these patients had significantly shorter overall survival (OS) and relapse-free survival (RFS). Furthermore, multivariate analysis showed that CD7+ with DNMT3A mutation was an independent risk factor for OS and RFS. Conclusion: CD7+ with DNMT3A mutation predicts a poor prognosis in AML patients, and the immunophenotype combined with molecular genetic markers can help to further refine the current risk stratification of AML.